Citrinin (CIT) determination in rice samples using a micro fluidic electrochemical immunosensor - Arevalo, Fernando Javier (2011)
The development of an electrochemical immunosensor incorporated in a micro fluidic cell for quantification of citrinin (CIT) mycotoxin in rice samples is described for the first time. Both CIT present in rice samples and immobilized on a gold surface electrodeposited on a glassy carbon (GC) electrode modified with a cysteamine self-assembled monolayer were allowed to compete for the monoclonal mouse anti-CIT IgG antibody (mAb-CIT) present in solution. Then, an excess of rabbit anti mouse IgG (H + L) labelled with the horseradish peroxidase (secAb-HRP) was added, which reacts with the mAb-CIT which is in the immuno-complex formed with the immobilized CIT on the electrode surface. The HPR, in the presence of hydrogen peroxide (H2O2) catalyzes the oxidation of catechol (H2Q) whose back electrochemical reduction was detected on a GC electrode at -0.15 V vs Ag/AgCl by amperometric measurements. The current measured is proportional to the enzymatic activity and inversely proportional to the amount of CIT present in the rice samples. This immunosensor for CIT showed a range of work between 0.5 and 50 ng mL -1. The detection (LOD) and the quantification (LOQ) limits were 0.1 and 0.5 ng mL-1, respectively. The coefficients of variation intra- and inter-assays were less than 6%. The electrochemical detection could be done within 2 min and the assay total time was 45 min. The immunosensor was provided to undertake at least 80 determinations for different samples with a minimum previous pre-treatment. Our electrochemical immunosensor showed a higher sensitivity and reduced analysis time compared to other analytical methods such as chromatographic methods. This methodology is fast, selective and very sensitive. Thus, the immunosensor showed to be a very useful tool to determine CIT in samples of cereals, mainly rice samples.